#TITLE_ALTERNATIVE# - (NIM 10105063), ZULKARNAIN
Interpolation can be used to construct a function that passes certain points. Moreover, interpolation can also be used to approximate a function in order to make this function easy to analyze. There are several methods of interpolation. In this final project, we will discuss about a classical interpolation method, namely Lagrange Interpolation which uses polynomials as its interpolatant function. We are concerned with two main issues : the existence of the solution and the error caused by the interpolation method. After that, we will discuss about the extension of this Lagrange Interpolation, namely Hermite Interpolation and Semi Hermite Interpolation.